Evaluation of the vaginal flora in pregnant women receiving opioid maintenance therapy: a matched case-control study. Issue 1 (December 2016) - Farr, Alex; Kiss, Herbert; Hagmann, Michael; Holzer, Iris; Kueronya, Verena; Husslein, Peter; Petricevic, Ljubomir
Abstract Background Vaginal infections are a risk factor for preterm delivery. In this study, we sought to evaluate the vaginal flora of pregnant women receiving opioid maintenance therapy (OMT) in comparison to non-dependent, non-maintained controls. Methods A total of 3763 women with singleton pregnancies who underwent routine screening for asymptomatic vaginal infections between 10 + 0 and 16 + 0 gestational weeks were examined. Vaginal smears were Gram-stained, and microscopically evaluated for bacterial vaginosis, candidiasis, and trichomoniasis. In a retrospective manner, data of 132 women receiving OMT (cases) were matched for age, ethnicity, parity, education, previous preterm delivery, and smoking status to the data of 3631 controls. The vaginal flora at antenatal screening served as the primary outcome measure. Secondary outcome measures were gestational age and birth weight. Results In the OMT group, 62/132 (47 %) pregnant women received methadone, 39/132 (29.5 %) buprenorphine, and 31/132 (23.5 %) slow-release oral morphine. Normal or intermediate flora was found in 72/132 OMT women (54.5 %) and 2865/3631 controls [78.9 %; OR 0.49 (95 % CI, 0.33–0.71);p < 0.001]. Candidiasis occurred more frequently in OMT women than in controls [OR 2.11 (95 % CI, 1.26–3.27);p < 0.001]. Findings were inconclusive regarding bacterial vaginosis (± candidiasis) and trichomoniasis. Compared to infants of the control group, those of women with OMT had a lower mean birth weight [MD −165.3 g (95 % CI, −283.6 to −46.9);p = 0.006]. Conclusions Pregnant women with OMT are at risk for asymptomatic vaginal infections. As recurrent candidiasis is associated with preterm delivery, the vulnerability of this patient population should lead to consequent antenatal infection screening at early gestation.